(untitled) (Journal of Health, Population and Nutrition, 2012)
Tuberculosis (TB) is a major public-health problem in India, having the highest number of incident and multidrug-resistant (MDR) TB cases. The study was carried out to appraise the prevalence of first-line anti- TB drug resistance in Mycobacterium tuberculosis (MTB) and its patterns among different types of TB patients from different settings in a province of North India. Of 3,704 clinical specimens, 345 (9.3%) were culturepositive, and drug-susceptibility testing was carried out for 301 MTB strains. A high level of primary and acquired drug resistance of MTB was observed in the region studied, with weighted mean of 10.5% and 28.08%, 12.81% and 29.72%, 17.12% and 29.94%, 11.97% and 27.84%, and 10.74% and 23.54% for rifampicin, isoniazid, streptomycin, ethambutol-resistant and MDR cases respectively. Drug resistance was significantly higher in pulmonary (p=0.014) and acquired drug-resistant TB cases (p<0.001). Any drug resistance (p=0.002) and MDR TB were significantly (p=0.009) associated with HIV-seropositive cases. An urgent plan is needed to continuously monitor the transmission trends of drug-resistant strains, especially MDR-TB strains, in the region. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9895 JHPN 2011; 29(6): 583-592